2016
DOI: 10.1515/scjme-2016-0011
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Viscous Liquids Spraying by the OIG and the Oil Configurations of an Effervescent Atomizer at Low Inlet Pressures

Abstract: In this work we studied the influence of the fluid injection configuration (OIG: outside-in-gas, OIL: outside-in-liquid) on the internal flows and external sprays parameters. We sprayed the viscous aqueous maltodextrin solutions (μ = 60 mPa·s) at a constant inlet pressure of the gas and the gas to the liquid mass flow ratio (GLR) within the range 2.5 to 20%. We found that the fluids injection has a crucial influence on the internal flows. The internal flows patterns for the OIG atomizer were the slug flows, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…However, when the liquid sheet comes in contact with the encircling air causes a wave disturbance in the liquid sheet and once the wavelength reaches an optimum value fragments are generated in the sheet that will contract to ligaments due to the surface tension of the liquid and ultimately broken down into droplets [30]. The relation of diameter of the drop with respect to the properties of the liquid and air is given by D/δ ∝ We −0.5 (10) where, δ is thickness of the liquid sheet, We-Weber Number = ρU 2 δ/σ and U is the liquid sheet velocity.…”
Section: Disruption Of the Liquid Sheetmentioning
confidence: 99%
“…However, when the liquid sheet comes in contact with the encircling air causes a wave disturbance in the liquid sheet and once the wavelength reaches an optimum value fragments are generated in the sheet that will contract to ligaments due to the surface tension of the liquid and ultimately broken down into droplets [30]. The relation of diameter of the drop with respect to the properties of the liquid and air is given by D/δ ∝ We −0.5 (10) where, δ is thickness of the liquid sheet, We-Weber Number = ρU 2 δ/σ and U is the liquid sheet velocity.…”
Section: Disruption Of the Liquid Sheetmentioning
confidence: 99%
“…They reported that burning synthesis gas leads to decreased performance by about 5% and to increased mass hourly consumption by 120 % [17]. Few researchers reported that the fluids injection has a crucial influence on the internal flows [18]. It is reported that the combustion duration of fuel increased significantly even with smaller concentration of honge oil in the fuel blend.…”
Section: Fig 1 Honge Treementioning
confidence: 99%
“…Kapilan, N., et al, [17] observed that the fuel mixture results in engine performance close to diesel operation at the higher injector nozzle opening pressure. Few researchers reported that fluid injection has a significant impact on internal flows [18].…”
Section: Introductionmentioning
confidence: 99%